Fabrication and characterization of hydrogel nanoparticles - Chen, Xiao Wei (Nanyang Technological University, 2023)
The conventional microparticles drug delivery systems have its limitations and through the usage of fabricating drugs into nanoparticles will reduce the disadvantages of conventional drug delivery system. As such, more in-depth research and characterizing of nanoparticles must be done to ensure the efficiency and effectiveness of the drugs. There are different polymers that have been used to fabricate nanoparticles in drug delivery as well as different methods for the fabrication of the particles. In this study, we will be focusing on the Poly(ethylene glycol) diacrylate polymer with the use of emulsion polymerization method for the fabrication. The current area of focus for this project will be on Poly(ethylene glycol) diacrylate hydrogel nanoparticles used in drug delivery system. The research will be divided into the fabrication of said hydrogel nanoparticles as well as the characterizing of the nanoparticles. The two methods of characterizing will be conducted through varying the concentration of the polymer solution, the aqueous phase, as well as the amplitude of the sonicator in the fabrication steps. This is to study how different sizes and stiffness will affect the cellular uptake as well as the effectiveness of the fabricated drugs. The first step of the process was able to fabricate PEGDA hydrogel nanoparticles, however in the characterizing process, the results showed a limitation to how the current parameters can affect the size of the particles, hence more research, experiments as well as better equipment are required for the characterizing steps. There are other factors that could be adjusted to observe how the particles sizing are affected before testing the cellular uptake using cultured cells.